A novel and selective silk fibroin fragmentation method. Issue 28 (6th July 2021) - Agostinacchio, Francesca; Maniglio, Devid; Callone, Emanuela; Migliaresi, Claudio; Dirè, Sandra; Motta, Antonella
Abstract : Silk fibroin precise cleavage on specific amino acid sites using collagenase type G enzyme leads to precise silk fibroin fragmentation and, thus, lower molecular weight materials whose length and properties can be tuned with the enzyme concentration. Abstract : In the tissue-engineering field silk fibroin can be tailored to the target applications by modifying its secondary structure and molecular weight, and functionalizing the molecule with specific active groups linked to the amino acid side chains. To better tune the silk fibroin molecular weight and structural properties, we propose the creation of a lower molecular weight fibroin-derived material through a selective and tunable enzymatic attack on the fibroin chain. Cleavage at specific amino acid sites leads to precise silk fibroin fragmentation and, thus, lower molecular weight materials whose length and properties can be tuned with the enzyme concentration. The cleavage increased the presence of free amino groups, hence reactivity, and aqueous solutions of the resulting polymer remained stable for up to seven days. Films of fragmented fibroin were prepared and characterized, demonstrating that the fragmentation did not affect β-sheet formation after methanol treatment, but differences were detected after the water-vapor annealing process, confirmed by structural and thermal analyses. The adopted fragmentation method is fast, controllable and precise, allowing the creation of a silk-derived material class that is stable in water, with a tunable molecular weight and secondary structure rearrangements, and is thus a versatile tool for the further tunability and modulation of bioengineered constructs.